Multi-method Analysis of Avian Eggs as Grave Goods: Revealing Symbolism in Conversion Period Burials at Kukruse, NE Estonia. (3rd April 2018) - Jonuks, Tõnno; Oras, Ester; Best, Julia; Demarchi, Beatrice; Mänd, Raivo; Presslee, Samantha; Vahur, Signe
ABSTRACT: Eggshells are unusual finds in the Iron Age of eastern Europe (500 BC–1200 AD) deserving extra attention in terms of analysis as well as interpretation. This paper discusses two rare eggshell finds, discovered in female burials at the conversion period (12th–13th century AD) cemetery at Kukruse, NE Estonia. Our multianalytical study combining FT-IR, SEM(-EDS), microscopy and ZooMS provides an overview of methods applicable for identifying egg species, their predepositional history and curation. Based on the analytical results and the comparative analysis of the content and context of these two burials, we argue that different aims and connotations lay behind depositing eggs as burial goods, allowing well-supported interpretations of both pagan and Christian religious worldviews simultaneously.